Synergistic action between a synthetic cannabinoid compound and tramadol in neuropathic pain rats - Quiñonez-Bastidas Geovanna Nallely; Osuna-Martínez Ulises; Reda-Licea Ana Laura; López-Ortíz Manuel; Regla Ignacio; Navarrete Andrés (Acta Pharmaceutica)
In the present study the interaction of cannabinoid, PhAR-DBH-Me [(R, Z)-18-((1S,4S)-5-methyl-2,5-diazabicyclo[2.2.1]heptan-2-yl)-18-oxooctadec-9-en-7-ylphenyl-acetate] and tramadol in two neuropathy models, as well as their possible toxic effects, was analyzed. The anti-allodynic effect of PhAR-DBH-Me, tramadol, or their combination, were evaluated in neuropathic rats. Furthermore, the effective dose 35 (as the 35 % of the anti allodynic effect) was calculated from the maximum effect of each drug. Moreover, the isobolographic analysis was performed to determine the type of interaction between the drugs. A plasma acute toxicity study was carried out to assess the hepatic, renal, and heart functions after an individual or combined administration of the drugs, as well as histology using the hematoxylin-eosin or Masson-trichome method. PhAR-DBH-Me, tramadol, and their combination produced an antiallodynic effect on spinal nerve ligation (SNL) and cisplatin-induced neuropathic pain in rats. Moreover, PhAR-DBH-Me and tramadol combination showed a synergistic interaction in neuropathic pain rats induced by SNL but not for cisplatin-induced neuropathy. On the other hand, changes in renal and hepatic functions were not observed. Likewise, analysis of liver, kidney and heart histology showed no alterations compared with controls. Results show that the combination of PhAR-DBH-Me and tramadol attenuates the allodynia in SNL rats; the acute toxicology analysis suggests that this combination could be considered safe in administered doses.